Diagnosis and management of vasovagal syncope: A comprehensive review - Veliawan, Zhafran; Rizal, Ardian (Universitas Brawijaya, 2026)
Syncope is a distinct type of transient loss of consciousness characterized by rapid onset and complete spontaneous recovery. Syncope is categorized into three different kinds according to the 2018 European Society of Cardiology guidelines. Different types of syncope ultimately converge on a common pathophysiological occurrence: global cerebral hypoperfusion, resulting from the circulatory system's inability to maintain blood pressure at a level sufficient to provide adequate cerebral perfusion. Vasovagal syncope, often referred to as the